Optimal use of lipid-lowering therapy after acute coronary syndromes: A Position Paper endorsed by the International Lipid Expert Panel (ILEP) - Banach, Maciej; Penson, Peter E; Vrablik, Michal; Bunc, Matjaz; Dyrbus, Krzysztof; Fedacko, Jan; Gaita, Dan; Gierlotka, Marek; Jarai, Zoltan; Magda, Stefania Lucia; Margetic, Eduard; Margoczy, Roman; et al. (Pharmacological research, 2021)
Atherosclerotic cardiovascular disease (ASCVD) and consequent acute coronary syndromes (ACS) are substantial contributors to morbidity and mortality across Europe. Much of these diseases burden is modifiable, in particular by lipid-lowering therapy (LLT). Current guidelines are based on the sound premise that with respect to low density lipoprotein cholesterol (LDL-C), "lower is better for longer", and the recent data have strongly emphasized the need of also "the earlier the better". In addition to statins, which have been available for several decades, the availability of ezetimibe and inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9) are additional very effective approach to LLT, especially for those at very high and extremely high cardiovascular risk. LLT is initiated as a response to an individual's calculated risk of future ASCVD and is intensified over time in order to meet treatment goals. However, in real-life clinical practice goals are not met in a substantial proportion of patients. This Position Paper complements existing guidelines on the management of lipids in patients following ACS. Bearing in mind the very high risk of further events in ACS, we propose practical solutions focusing on immediate combination therapy in strict clinical scenarios, to improve access and adherence to LLT in these patients. We also define an 'Extremely High Risk' group of individuals following ACS, completing the attempt made in the recent European guidelines, and suggest mechanisms to urgently address lipid-medicated cardiovascular risk in these patients.
Keywords: anticholesteremika; Combination therapy; Statins; Humans; PCSK9 inhibitors; PCSK9 inhibitory; management nemoci; lipidy; ateroskleróza; lidé; Ezetimibe; Anticholesteremic Agents; Effectiveness; Acute Coronary Syndrome; ezetimib; Atherosclerosis; Lipids; Safety; akutní koronární syndrom; Disease Management; PCSK9 Inhibitors